The Modernization Factors of Dayah Jeumala Amal's Curriculum Pidie Jaya Regency, Aceh Province - Abd Mukti; Siti Halimah; Firdaus Syah (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This study aims to describe the factors behind the modernization of the Dayah Jeumala Amal curriculum, Pidie district, Aceh province. This study uses a qualitative method with a naturalistic approach. The research location is Dayah Jeumala Amal Lueng Putu, Pidie Jaya Regency, Aceh Province. Data collection techniques used are interviews, observations, and document studies. Data management consists of data reduction, data presentation, data analysis, data validity techniques of research results. The results showed that the factors behind the modernization of the Dayah Jeumala Amal curriculum, Pidie Jaya district, Aceh province consisted of internal factors, namely the emergence of awareness among the founders and the surrounding community to advance education in the Aceh region in accordance with the needs and developments of the times, and external factors. related to the modernization of Islamic education that emerged in other Islamic worlds such as Egypt, Turkey and India as well as the influence of modernization ideas in the early 20th century AD.